Nomenclatural note on the homonymy between the octocoral genus Dendrobrachia Brook 1889 and the entoproct phylum Dendrobrachia Xian-Guan, Bergström, Xio-Ya and Jie 2006 - Pante, Eric (Zootaxa, 2016)
Dendrobrachia was proposed by Xian-Guan et al. (2006) as the name of a new phylum of entoproct-like animals from the Lower Cambrian (Yunnan Province, China). This name was however preoccupied by the octocoral Dendrobrachia Brook 1889, which position within the subclass Octocorallia is currently uncertain (Opresko and Bayer 1991; Berntson et al. 1999, 2001). Based on the principles of homonymy and priority (Articles 52 and 23, respectively; ICZN 1999), a substitute name for the entoproct Dendrobrachia is necessary, and I propose Dendrobrachion (based on the Greek brachion, for arm).